Teacher’s Work Motivation at SD Negeri 3 Mulyaguna, Teluk Gelam, Ogan Komering Ilir - Susilawati, Susilawati (PPSDP International Journal of Education, 2024)
The aim of this research is to describe the work motivation of teachers at SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI, the factors that influence the motivation of teachers at SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI, and the efforts of the principal of SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI to motivate elementary school teachers. SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI is carrying out duties at SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI. This research uses a qualitative research method with a phenomenological approach. Data was collected through interviews, observation, and documentation studies. The researchers then analyzed the results of this research by reducing the data, displaying the data, and verifying the data. The results of this research show that the work motivation of teachers working at SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI Mulyaguna Regency is good. Factors that influence teacher work motivation at SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam Kabupaten OKI include guidance and encouragement, will, expertise, willingness, professionalism, responsibility, and obligation in carrying out their duties. Efforts by the head of SD Negeri 3 Mulyaguna Kecamatan Teluk Gelam kabupaten OKI to motivate teachers with comfort in the teaching place, opportunities to take part in education and training, seminars, workshops, opportunities to develop careers, provide incentives or wages, pay attention to teachers, and provide rewards and awards for teachers who excel.